PENGARUH RISIKO KREDIT DAN LIKUIDITAS TERHADAP RASIO KECUKUPAN MODAL PADA PT. BPR SWADAYA ANAK NAGARI PERIODE 2015-2019 - Mardahleni Mardahleni; Eko Putra (ITB AAS INDONESIA Surakarta, 2022)
Capital Adequacy Ratio (CAR) is one of the indicators used to measure bank capital adequacy. Capital for banks is used to absorb losses from banking activities and as the basis for several policies issued by banks. This research was conducted to determine (1) the effect of Non Performing Loan and Loan to Deposit Ratio on Capital Adequacy Ratio partially at PT. BPR SwadayaAnakNagari period 2015 - 2019. (2) the effect of the Non Performing Loan and Loan to Deposit Ratio on the Capital Adequacy Ratio simultaneously at PT. BPR SwadayaAnakNagari for the 2015 - 2019 period. The results of this study show that (1) Partially the Non-Performing Loan and Loan to Deposit Ratio variables have a positive and significant effect on the Capital Adequacy Ratio. (2) Simultaneously the variables of Non Performing Loan and Loan to Deposit Ratio have a positive and significant effect on the Capital Adequacy Ratio. The value of the coefficient of determination (R-Square) is 0.766. From this value, it can be interpreted that the Non-Performing Loan (X1) and Loan to Deposit Ratio (X2) to the Capital Adequacy Ratio (Y) are 76.6%. Meanwhile, the remaining 23.4% is influenced by other factors not examined in this study. Keywords: Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR)